2019
DOI: 10.1002/ecs2.2570
|View full text |Cite
|
Sign up to set email alerts
|

Demography of evergreen and deciduous oaks in a mixed oak savanna: insights from a long‐term experiment

Abstract: The co-existence of evergreen and deciduous oaks in Mediterranean-climate savannas has motivated comparative studies on species' physiological adaptations to light and drought, establishment niche differences in acorn production, dispersal and seedling herbivory, and differential sapling tolerance of ungulate browsing. Understanding how species' differences collectively affect co-occurrence or segregation requires long-term studies that consider multiple life stages. We compare survival, height growth, and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Our results are consistent with the reported generalized dependence on facilitation of recruitment in Quercus species in ecosystems stressed by climate and herbivores [8,10,13,14,18]. Although we did not studied the facilitation mechanisms of nurses, our results showed that positive association of recruits with nurse plants exists, and that this association was stronger for saplings than for juveniles, as occurs in other species [13].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with the reported generalized dependence on facilitation of recruitment in Quercus species in ecosystems stressed by climate and herbivores [8,10,13,14,18]. Although we did not studied the facilitation mechanisms of nurses, our results showed that positive association of recruits with nurse plants exists, and that this association was stronger for saplings than for juveniles, as occurs in other species [13].…”
Section: Plos Onesupporting
confidence: 91%
“…In Q. ilex, recruitment occurs in full sun only when annual precipitation is 700 mm or more [10], but as precipitation decreases, seedlings need shade to compensate for evapotranspiration, until reaching a lower limit of annual precipitation, around 250 mm, when the water deficit can no longer be compensated by the shade [10,12]. In the wild, nurse plants facilitate the establishment of seedlings in many Quercus species under Mediterranean climate conditions because they improve soil conditions, reduce predation on seeds and seedlings, and provide shade that favors a positive water balance of seeds and young plants [8,[13][14][15][16][17][18]. However, Quercus seedlings need light to grow, so the intense shade that favors recruitment under high evaporative demand makes their subsequent development to seedlings and juveniles difficult or even impossible [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, evergreen oaks have showed greater herbivory resistance partly due to their lower palatability (Davis, Tyler, & Mahall, ; Griffin, ). Our results show higher seedling survival rates for Q. agrifolia as compared to Q. lobata , in line with previous studies (see review Perea et al, ; Tyler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, Q. lobata showed higher probability of browsing damage occurring and at higher intensity (higher probability of high and maximum damage, Figure 3b) compared to Q. agrifolia, in line with previous studies (Griffin, 1971; Tyler et al, 2006; Perea et al, 2017). This is partly due to the higher herbivory resistance of evergreen oaks, which typically have lower palatability (Griffin, 1971; Perea et al, 2017; Davis et al, 2019), but also because Q. agrifolia seedlings were mainly found in nurse microsites (under shrubs), in contrast to Q. lobata in which seedlings were significantly linked to microsites under tree canopies, which have denser shade and, thus, favored Q. lobata , a shade‐tolerant species (Niinemets and Valladares, 2006). Trees are frequently visited by large animals looking for shelter and forage (Joffre et al, 1988; Callaway and Davis, 1998; Tews et al, 2004) and therefore seedlings growing under them are typically more exposed to browsing (Connell, 1971; Perea et al, 2017; López‐Sánchez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, oak woodlands are threatened by continuous failure of tree recruitment (Manning et al, 2006; Tyler et al, 2006; Gibbons et al, 2008; Underwood et al, 2009; López‐Sánchez et al, 2016) caused by significant anthropogenic impacts over the last decades (Steffen et al, 2015). The lack of explicitly planned conservation objectives to counter these impacts (Roche et al, 2012) has led to widespread degradation of oak woodlands (Tyler et al, 2006; López‐Sánchez et al, 2016) and placed these systems under threat (Marañón et al, 2009; Underwood et al, 2009; Davis et al, 2019). These anthropogenic impacts have quickly modified the abiotic (e.g., climate disruption) and biotic conditions (e.g., diseases, pests, overgrazing) prevailing in ecosystems such as oak woodlands, increasing their stress intensity since the mid‐20th century (Blondel and Aronson, 1999; Underwood et al, 2009; López‐Sánchez et al, 2017; Sapp et al, 2019).…”
Section: Introductionmentioning
confidence: 99%